La conférence de Berlin de juin 1976 : analyse du discours communiste - Marcou, Lilly (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
The Berlin Congress would seem to have completed the historic sequence of Congresses begun in 1957 with the Moscow world congress of Communist parties. It represents a turning point in the history of the Communist movement, especially as it pertains to Europe. Its long and laborious preparatory phase as well as the density and contradictory nature of its proceedings provide a new image of European Communism in crisis by bringing together a diversity of governing parties. Certain among the latter are all-powerful in their countries, others, important opposition forces involved closely or indirectly in the process of governing, while others are either underground or represent an infinitely small portion of their respective electorates. The Berlin Congress was the theater of debates containing the potentialities of conflict that animate the European Communist parties. It confirmed and stabilized a major phenomenon whose origins are to be found at the world Communist Party Congress of 1969 - Eurocommunism.